Social Work and Human Rights: Uncrossed Paths Between Exposure, Engagement, Lens, and Methods in Professional Practice - Maria Irene Carvalho; Cristina Albuquerque; Pedro Borrego (Social Sciences)
This article intends to demonstrate the interconnections between exposure, engagement, human rights (HRs) lens, and methods in social work. To achieve these aims, we used HRXSW, HRESW, HRLSW, and HRMSW index scales to carry out a survey amongst Portuguese social workers. This survey was sent to 4079 registered members (100%) of the Portuguese professional association, of which 259 were valid responses (6.3%). The results of this pilot study show that professionals are exposed to HR in the education system and in the professional practice and that the level of engagement with HR is strong. Professionals revealed that social problems and rights violations played a prominent role during their practices with clients; however, contradictions are noticed in relation with intervention methods. Their methods are mostly informed by individual rights and personal empowerment, collaboration, and accountability and, to a lesser extent, by non-discrimination, micro and meso approach, and activism. We conclude that professionals have the knowledge and courage to consolidate and promote HR; however, in order to advocate for and promote structural social changes that lead to the full realization of an HR utopia, they need to use methods based on structural and collective approaches.